PAULOWNIA Sieb.&Zucc: A NEW EXOTIC GENUS FOR MULTI-PURPOSE USES IN KASTAMONU - TURKEY - Ayan, Sezgin; Sağlam, İrem; Sıvacıoğlu, Ahmet (Decision Support for Multiple Purpose Forestry, April 23-25, 2003, Vienna - Austria, 2003)
Paulownia is a native and fast growing tree in China. Nine species used for medicinal purposes, seed oils, fodder, manure, charcoal, reclamation of mined land and other are Paulownia fortunei, P. tomentosa, P. fagesii, P. australi, P. elongata, P. taiwaniana, P. albiphloea, P. catalpifolia and P. kawakamii,. In addition, Paulownia wood is widely used for various purposes, for example, house construction, paper pulp, furniture making, farm implements, music instrument and handicrafts. Paulownia genus has also an unique biological character, its root system grows in deep earth and its crown develops in loose structure, which enable it suitable to be intercropped with crops or mixed planting of other shade-tolerant trees. So, Paulownia is also a good tree for development of agro forestry.
Keywords: Paulownia, Origin, Adaptation, Multi-Purpose, Kastamonu, Turkey